Possible Function of Molecular Chaperones in Diseases Caused by Propagating Amyloid Aggregates - Lazarev, Vladimir F.; Mikhaylova, Elena R.; Guzhova, Irina V.; Margulis, Boris A. (Frontiers in Neuroscience, 2017)
The vast majority of neurodegenerative pathologies stem from the formation of toxic oligomers and aggregates composed of wrongly folded proteins. These protein complexes can be released from pathogenic cells and enthralled by other cells, causing the formation of new aggregates in a prion-like manner. By this mechanism, migrating complexes can transmit a disorder to distant regions of the brain and promote gradually transmitting degenerative processes. Molecular chaperones can counteract the toxicity of misfolded proteins. In this review, we discuss recent data on the possible cytoprotective functions of chaperones in horizontally transmitting neurological disorders.